Control of PMSG based variable speed wind energy conversion system connected to the grid with PI and ADRC approach - Youssef Barradi; Khalida Zazi; Malika Zazi; Naoufel Khaldi (Institute of Advanced Engineering and Science, 2020)
This paper presents the modeling and simulation of wind energy Conversion System using the Permanent Magnet Synchronous Generator (PMSG). The objectives are: to extract the maximum power of the wind speed by controlling the electromagnetic torque of the PMSG, to maintain constant the DC-link voltage despite the wind speed variations and to attain the unity power factor. In order to ensure a regulation with high performance and a good robustness against the internal and the external disturbances, a new control strategy called the Active Disturbance Rejection Control (ADRC) is used. Therefore, the Analysis and simulation of the ADRC and PI controllers are developed with MATLAB/Simulink software. The performance of these controllers is compared in term of references tracking, robustness and grid faults.